COMPREHENSIVE MODEL OF COUNTERACTION AGAINST UNMANNED AIRCRAFT BY FORCES AND MEANSMILITARY UNIT ON THE PROTECTION OF AN IMPORTANT GOVERNMENT FACILITY (NUCLEAR INSTALLATION) - Rosliakov, Oleksii; Horielyshev, Stanislav (Honor and Law, 2025)
A comprehensive three-level model of countering unmanned aerial vehicles for the protection of nuclear installations by the National Guard of Ukraine is presented. The comprehensive model consists of three parts: a model of the buffer zone determination process, a model of unmanned aerial vehicles detection, and a model of their destruction and/or neutralization. For the first time, a method for calculating the buffer zone is proposed, taking into account the characteristics of unmanned aerial vehicles, response time, and reachable zones of mobile fire groups. The possibility of using bistatic radar in the early target detection zone is substantiated. The process of destroying unmanned aerial vehicles was modeled using a stochastic mass service system of the M/M/n/m type with exit from the queue. The results of the study make it possible to increase the effectiveness of the combat use of mobile fire groups in conditions of limited resources and adapt the defense system to modern threats.